Optimization of auto-tuning of programs using neural networks - Doroshenko, А.Yu.; Ivanenko, P.A.; Novak, O.S. (PROBLEMS IN PROGRAMMING, 2018)
Auto-tuning of programs is a method of self-tuning of internal parameters of the program, affecting its speed, in order to achieve high performance indicators, but it can take a lot of time for testing. In this paper, we propose to improve the method of auto-tuning of programs using neural network algorithms and statistical simulation. The automatic learning of the program model on the results of the "traditional" tuning cycles with the subsequent replacement of some auto-tuner calls with an evaluation from the approximation model allows to significantly accelerate the search for the optimal program variant. Problems in programming 2017; 2: 40-47